PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD: STUDI REVIEW - Suci Ramanda; Syaila Nurifki; Masniladevi Masniladevi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Mathematical problem-solving ability is one of the basic skills that needs to be developed from elementary school level, as students are not only required to calculate, but also to understand problems, choose appropriate solution strategies, carry out solution steps, and recheck their answers. One learning model that is relevant to support this ability is Problem Based Learning, because learning begins with contextual problems that are close to students’ daily lives. This article aims to review the implementation of the Problem Based Learning model on elementary school students’ mathematical problem-solving ability. This study used a review method with a simple systematic literature review pattern. The data were obtained from 22 scientific articles published between 2021 and 2026 that were relevant to PBL, elementary mathematics learning, and mathematical problem-solving ability. The articles were analyzed descriptively and qualitatively by considering article characteristics, research methods, subjects, forms of PBL implementation, supporting media, and research findings. The review results show that the implementation of PBL tends to have a positive effect on elementary school students’ mathematical problem-solving ability. PBL helps students become more active in understanding problems, discussing ideas, developing strategies, solving problems, and explaining their thinking processes. The implementation of PBL becomes more effective when supported by clear problems, appropriate learning media, teacher guidance, and good classroom management. This review indicates that PBL is suitable as an alternative mathematics learning model to develop elementary school students’ mathematical problem-solving ability. ABSTRAK Kemampuan pemecahan masalah matematis merupakan salah satu kemampuan dasar yang perlu dikembangkan sejak jenjang sekolah dasar, karena siswa tidak hanya dituntut mampu menghitung, tetapi juga memahami masalah, memilih strategi penyelesaian, melaksanakan langkah penyelesaian, dan memeriksa kembali jawaban. Salah satu model pembelajaran yang relevan untuk mendukung kemampuan tersebut adalah Problem Based Learning karena pembelajaran dimulai dari masalah kontekstual yang dekat dengan kehidupan siswa. Artikel ini bertujuan untuk mengkaji penerapan model Problem Based Learning terhadap kemampuan pemecahan masalah matematis siswa sekolah dasar melalui studi review. Metode yang digunakan adalah studi review dengan pola systematic literature review sederhana. Data diperoleh dari 22 artikel ilmiah yang dipublikasikan pada rentang tahun 2021–2026 dan relevan dengan topik PBL, pembelajaran matematika SD, serta kemampuan pemecahan masalah matematis. Artikel dianalisis secara deskriptif-kualitatif dengan memperhatikan karakteristik artikel, metode penelitian, subjek, bentuk penerapan PBL, media pendukung, dan hasil penelitian. Hasil review menunjukkan bahwa penerapan PBL memiliki kecenderungan positif terhadap kemampuan pemecahan masalah matematis siswa SD. PBL membantu siswa lebih aktif dalam memahami soal, berdiskusi, menyusun strategi, menyelesaikan masalah, dan menjelaskan proses berpikirnya. Penerapan PBL juga lebih efektif ketika didukung oleh masalah yang jelas, media pembelajaran yang sesuai, bimbingan guru, serta pengelolaan kelas yang baik. Kajian ini menunjukkan bahwa PBL layak digunakan sebagai salah satu alternatif model pembelajaran matematika untuk mengembangkan kemampuan pemecahan masalah matematis siswa sekolah dasar.